2000
DOI: 10.1046/j.1420-9101.2000.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional mechanisms of an inducible defence in tadpoles: morphology and behaviour influence mortality risk from predation

Abstract: In many amphibian larvae a suite of morphological and behavioural characters varies together in an induced defence against predators, but it remains unclear which features are functionally related to defence. We independently manipulated behaviour and morphology in tadpoles of Hyla versicolor and assessed their consequences for swimming performance and predator escape. Data on burst swimming showed that tadpoles which accelerated rapidly were elongate, with shallow bodies and tails. Predator escape was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
161
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(178 citation statements)
references
References 52 publications
10
161
2
Order By: Relevance
“…Phenotypic plasticity in frog larvae Frog tadpoles are an effective system for exploring the ecology of phenotypic plasticity. Frequently, predators induce tadpoles to reduce their foraging activity, which reduces detection by predators [62]. Predators also induce relatively larger tails and smaller bodies in tadpoles ( Figure I) [62], which reduce capture by predators [63] owing to faster swimming abilities and because a large tail lures predator strikes away from the vulnerable body [64].…”
Section: Indirect Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic plasticity in frog larvae Frog tadpoles are an effective system for exploring the ecology of phenotypic plasticity. Frequently, predators induce tadpoles to reduce their foraging activity, which reduces detection by predators [62]. Predators also induce relatively larger tails and smaller bodies in tadpoles ( Figure I) [62], which reduce capture by predators [63] owing to faster swimming abilities and because a large tail lures predator strikes away from the vulnerable body [64].…”
Section: Indirect Interactionsmentioning
confidence: 99%
“…Frequently, predators induce tadpoles to reduce their foraging activity, which reduces detection by predators [62]. Predators also induce relatively larger tails and smaller bodies in tadpoles ( Figure I) [62], which reduce capture by predators [63] owing to faster swimming abilities and because a large tail lures predator strikes away from the vulnerable body [64]. However, both defenses come at the cost of slower growth [65], because predatorinduced tadpoles have smaller mouthparts [66] and shorter, less efficient intestines, and spend less time foraging [67].…”
Section: Indirect Interactionsmentioning
confidence: 99%
“…However, other studies have shown that tadpoles usually do not have a chance to generate defensive responses (ZOTTOLI et al 2001) or increase their swimming speed before being attacked by an aquatic predator ( VAN BUSKIRK & MCCOLLUM 2000a, LUQUET et al 2011. Experimental manipulations of tadpoles with tail damage have revealed that swimming performance is affected only after large tail segments are removed (HOFF & WASSERSUG 2000, VAN BUSKIRK & MCCOLLUM 2000b).…”
mentioning
confidence: 99%
“…A high level of tail damage was found by BLAIR & WASSERSUG (2000) in a wild population of tadpoles. Tail damage in tadpoles can be caused by vertebrates, such as fish, turtles and salamanders, and by invertebrates, such as crayfish and dragonfly larvae (WILBUR & COLLINS 1973, CALDWELL et al 1980, VAN BUSKIRK & MCCOLLUM 2000a, VAN BUSKIRK et al 2003, WILSON et al 2005.…”
mentioning
confidence: 99%
See 1 more Smart Citation